A systematic review of the international assessment systems for urban sustainability. (August 2019) - Pedro, J; Reis, A; Duarte Pinheiro, M; Silva, C
Abstract: Planning and managing the rapidly growing cities in a manner that delivers a balanced solution for their environmental, social and economic long-term development constitutes one of the grand challenges of societies. In the urban planning field, several sustainability assessment systems emerged to guide the planning process towards these goals. After two decades of existence, there is a need to further analyze the lessons learned from the application of these systems and discuss the pathways towards more sustainable societies. This paper provides a literature review of the most widely used urban sustainability assessment systems: BREEAM Communities, LEED Neighborhoods, CASBEE Urban Development, Green Star Communities, and DGNB Urban Districts. Here, we analyzed 124 publications on the topic published between 2015-2018, using the selected assessment systems as keywords. This study revealed that there is a need for context customization of global targets into local actionable measures; involvement of regulatory bodies to ensure the successful application of such systems; and, consideration of socioeconomic factors as the assessment is still very focused on the environmental impact. This study provides insights for practitioners and researchers on the existing systems to assess urban sustainability and pathways for future research.